Pengaruh Strategi Digital Marketing dan Citra Merek terhadap Keputusan Pembelian Konsumen pada Coffee Shop di Bangkinang - Andri Nofiar. Am; Supriati; Tri Handayani; Rahmad Akbar; Dzulhijjah Yetti (DIBINOM : Digital Business, Economic Jurnal, 2026)
This study offers a comprehensive analysis of the factors driving consumer behavior within the vibrant coffee shop industry in Bangkinang, specifically focusing on the interplay between digital marketing strategies and brand image. Employing a quantitative associative research design, the investigation gathered empirical data from 98 purposively selected respondents. The analytical process involved multiple linear regression, preceded by rigorous testing for validity, reliability, and classical assumptions to ensure data integrity. The findings reveal a compelling narrative: while a well executed digital marketing strategy significantly boosts purchasing decisions, it is the strength of a brand’s image that emerges as the most dominant catalyst in the consumer's final choice. Both variables, when acting in synergy, provide a robust explanation for the fluctuations in local purchasing trends. These results underscore a critical strategic insight for entrepreneurs: simply having a digital presence is insufficient. To thrive in a competitive landscape, coffee shop owners must prioritize the cultivation of a distinctive and trustworthy brand identity. By integrating sophisticated digital outreach with a resonant brand story, businesses can effectively enhance their market appeal and secure long term consumer loyalty. Consequently, this research advocates for a balanced strategic approach to maximize business competitiveness in the modern digital era.